(untitled) (Experimental biology, 2023)
Chronic inflammatory diseases are one of the leading causes of death in the world. A number of pathological conditions are associated with chronic inflammation, such as chronic obstructive pulmonary disease, rheumatoid arthritis, metabolic syndrome, type 2 diabetes mellitus, cardiovascular, chronic kidney disease, cancer, neurodegenerative and autoimmune diseases. To address a number of issues related to this problem, reliable models of chronic inflammation are needed. A number of chemical inductors of this state are known from the literature. One of them is interleukin-2. Roncoleukin is a dosage form of recombinant human interleukin-2. To date, few studies have been presented on changes at the tissue level under the influence of IL-2. In this work, we studied the patterns of morphological changes in the lungs, liver, kidneys, spleen, and thymus of CD-1 mice under the influence of low and high doses of Roncoleukin. We have shown that the drug contributes to an increase in the mass of the spleen by 2 times and a decrease in the mass of the thymus by 1.5 times. Roncoleukin has a stimulating effect on the immunocompetent compartment, leading to cell proliferation of T-dependent zones of the spleen and thymus cortex. In the visceral organs, under its action, a picture of a chronic inflammatory process develops.